A review on the states structure plan of Selangor 2035 : radial economic nucleus - Kadar Hamsa, Abdul Azeez; Ibrahim, Mansor; Ahmad Sarkawi, Azila; Zen, Irina Safitri; Mohd Ikbal, Nurul Ain Nazihah; Abdullah, Nur Shahida; Mohd Nor, Farah Husna (2020)
This article is a review of Selangor State Structure Plan 2035 that is in line with the preparation of the state’s 5years’ development plans. This review covers all items pertaining to the whole state development strategies, policies and indicatives areas. The review also commences if there is new or alterations on national plan policies or sectoral policies, which incorporated the alterations on policies at state level. It is in a way to incorporate the change of development trend intervened. The review of Selangor State Structure Plan 2035 consists of 46 policies, 160 strategies and 25 high impact proposals.